Properties of particleboard from sentang and Kenaf core / Mohd Sufian Sarif - Sarif, Mohd Sufian (2013)
In this study, the influences of board ratio and resin content (RC) on mechanical and physical properties of particleboard manufactured from sentang and kenaf core raw materials were determined. Sentang and kenaf core was used as alternative raw materials for particleboard manufacturing. Resin content of effect at (8,10,and 12%) and board ratio ( 50:50, 70:30, 100:0) were determine with in this situation . Board panels were tested for their mechanical strength including modulus of rapture (MOR), modulus of elasticity (MOE), internal bonding (lB) and physical properties thickness swelling (TS) were determined based on Malaysia (MS) standard. Mechanical and physical properties of particleboard were increased with of resin content. Strength and durability particleboard increased with sentang particle.